Large Bone Vertical Augmentation Using a Three‐Dimensional Printed TCP/HA Bone Graft: A Pilot Study in Dog Mandible. (21st February 2016) - Carrel, Jean‐Pierre; Wiskott, Anselm; Scherrer, Susanne; Durual, Stéphane
Abstract: Background: Osteoflux is a three‐dimensional printed calcium phosphate porous structure for oral bone augmentation. It is a mechanically stable scaffold with a well‐defined interconnectivity and can be readily shaped to conform to the bone bed's morphology. Purpose: An animal experiment is reported whose aim was to assess the performance and safety of the scaffold in promoting vertical growth of cortical bone in the mandible. Materials and methods: Four three‐dimensional blocks (10 mm length, 5 mm width, 5 mm height) were affixed to edentulous segments of the dog's mandible and covered by a collagen membrane. During bone bed preparation, particular attention was paid not to create defects 0.5 mm or more so that the real potential of the three‐dimensional block in driving vertical bone growth can be assessed. Histomorphometric analyses were performed after 8 weeks. Results: At 8 weeks, the three‐dimensional blocks led to substantial vertical bone growth up to 4.5 mm from the bone bed. Between 0 and 1 mm in height, 44% of the surface was filled with new bone, at 1 to 3 mm it was 20% to 35%, 18% at 3 to 4, and ca. 6% beyond 4 mm. New bone was evenly distributed along in mesio‐distal direction and formed a new crest contour in harmony with the natural mandibular shape. Conclusions: After two months of healing, the three‐dimensional printed blocks conducted new bone growth above its natural bed, up to 4.5 mm in a canine mandibular model. Furthermore, the new bone was evenly distributed in height and density along the block. These results are very promising and need to be further evaluated by a complete powerful study using the same model.